Anxiety, depression and cardiac anxiety in patients with implantable cardioverter-defibrillator according to gender and age - Isabelle Brigliadori Ignácio (Rev Rene, 2021)
Objective: to investigate the relationship between gender and age with symptoms of anxiety, depression and cardiac anxiety in patients with implantable cardioverter-defibrillator. Methods: cross-sectional study, with 76 patients with device attended in a university hospital. For data collection, a sociodemographic/clinical form and two validated scales were used in Brazil. In the analysis, the chi-square tests, exact Fischer and Mann-Whitney, with a significance level of 5% were adopted. Results: it was observed that the groups were homogeneous in terms of gender and age. Women presented higher medians in both anxiety and depression symptoms, with statistical significance. They also presented higher medians in symptoms of cardiac anxiety, but without statistical significance. Regarding age, no significant differences were found for the symptoms investigated. Conclusion: women presented more symptoms of anxiety and depression; however there was no relationship between the age of the patients and their symptoms.